The Causal Impact of Recruitment and Selection on the Perceived Performance of Teachers: Evidence from Public Secondary Schools in Phnom Penh, Cambodia - Chhy, Sothy; Kawai, Norimune (Angstrom Centre of Education, 2024)
In recent years, schools have investigated recruitment and selection practices to contribute to teacher performance, demonstrating that they value them. This quantitative study aimed to examine the impact of recruitment and selection practices on the performance of public secondary teachers in Phnom Penh, Cambodia, and the relationship between recruitment and selection and teacher performance. Our findings indicate that recruitment and selection impact teacher performance through processes and methods. It demonstrates the relationship between recruitment and selection and teacher performance through its critical exploration. The implications for our research contribute to recruitment and recruitment processes and methods that lead to teacher performance and the relationship between recruitment and teacher performance. The findings suggest a policy implication that there needs to be a greater need to improve recruitment and selection policies to enhance teacher performance. This study underlines the importance of recruitment and selection processes and methods as academic sources for researchers.